A Novel in Whole Cell Biosensor Incorporating Haematococcus pluvialis For Pesticide Detection in Water - Anna, Victorine Azie (2017)
There are major environmental and health concerns associated with pesticide presence in water. Conventional detection methods are expensive and laboratory based inadequate for in situ and real time monitoring of the pollutants. As such this research was focused on integrating Haematococcus pluvialis in a novel whole cell biosensor using de novo astaxanthin production as bioreporter for the detection of the pesticides atrazine, diuron and methyl parathion water. The microalga and astaxanthin cell contents were also determined spectrophotometrically. Immobilization of the cells was done in agarose gel and the response of the cells was measured in terms of percentage change in astaxanthin level by recording OD readings from a spectrophotometer with wavelength set at 482 nm before anf after rge exposure of the cells to the pesticide analyte. Optimum response of the biosensor towards the pesticides was 15 minutes after the exposure using day-3 cell culture at 2.50 x 105 cells/cuvette as cell density. The biosensor eas exposed to different 0.0010 mg/L, 5,000 mg/L and 10.0000 mg/L of each of the pesticides at the optimized pH 7.0. The biosensor showed high sensitivity to the range of concentration of the three pesticides used in this experiment with highest response recorded at pesticide used in this experiment with highest response recorded at pesticide concentration lower than 0.0010 mg/L. Therefore, the biosensor can be used as a screening system for environmental samples to indicate the presence of pesticides ad at the same time serves as a water safety warning system.